(untitled) (Scientific journal of the Fergana State University, 2026)
This article scientifically analyzes the main morpho-functional changes that occur in the human body during the aging process, including the decline in the activity of the nervous, cardiovascular, respiratory systems, as well as the musculoskeletal and muscular systems. During aging, physiological changes such as the slowdown of excitation and inhibition processes in the cerebral cortex, reduced contractile ability of the myocardium, decreased elasticity of blood vessels, and increased arterial blood pressure are observed.